Characteristics of performance in skeleton World Cup races - Bullock, N.; Hopkins, W. G.; Martin, D. T.; Marino, F. E. (Journal of Sports Sciences, 2009)
Little is known about performance characteristics in the Winter Olympic sport of skeleton, in which athletes push and then drive a sled down an ice track. In this study, official race times from World Cups held on 11 tracks over four competitive seasons were analysed with linear models for athletes placed in the top 10 (35 males in 22 races; 28 females in 25 races). Mean run time ranged from ~50 to ~70 s between tracks. Predictability of individual performance expressed as race-to-race correlations was modest (0.36 for males and females). Differences between tracks in run-to-run variability expressed as coefficients of variation (men: 0.19-0.56%; women: 0.24-0.89%) paralleled differences in popular opinion of technical difficulty of the tracks. There was an inconsistent and overall small relationship between push time and performance time on different tracks (range of correlations, 0.57 to -0.14; mean, 0.21). The home advantages of 0.15% for men and 0.32% for women were trivial and substantial respectively in relation to the smallest important performance changes of 0.18% and 0.23%, derived from race-to-race variability. In conclusion, skeleton athletes show less variability in performance time than athletes in other sports, but tracks vary substantially in difficulty and race outcomes are largely unpredictable.